Immersive Experience in the Metaverse: Implications for Tourism and Business - Komang Gita Krishna Murti; Gede Sri Darma; Luh Putu Mahyuni; A.A. Ngurah Eddy Supriyadinata Gorda (Politeknik Negeri Bandung, 2023)
By providing immersive and interactive experiences, the metaverse has been changing how tourists spend their vacation. It also presents new business challenges, such as gaming, marketing, education, and smart city industries. This research explores the opportunities and challenges presented by the metaverse in the tourism and business industries. This research also discusses the metaverse implications that can transform people's experience and consumption when traveling and consuming. A comprehensive literature review was conducted to explore the implications of the metaverse for the tourism and business industries. This study's findings reveal several examples of applying the metaverse and its implications. In addition, this study also discovered that the emergence of the metaverse significantly impacts the tourism and business sectors. In practice, the review findings make tourism and business stakeholders aware of the potential of this immersive technology. Tourism providers and business leaders might consider using the metaverse to promote tourism destination and their businesses and develop a system that can maximize the benefits of this immersive technology.